Respostas

A melhor resposta!
2014-02-06T19:57:34-02:00
N² + (n+1)² = (n +2)² 

n² + n² + 2n + 1 = n² + 4n + 4 

2n² + 2n + 1 = n² + 4n + 4 

2n² - n² + 2n - 4n + 1 - 4 = 0 

n² - 2n - 3 = 0 

Nas raízes, temos: 

n' = -1 

n'' = 3 

O -1 não serve, pois não é natural. A sequência é então: 

3 , 4 e 5. 

A soma é : 3 + 4 + 5 = 12 
1 5 1
2014-02-06T20:06:32-02:00
OLÁ

X² +(X +1)²=(+X+2)²=
 X²+X²+2.X.1+1²=X²+2.X.2+2²
2X²+2X+1 -X²-4X -4=
2X²-2X-3=
Δ =4-2.2.-3
Δ=4+12
Δ=16
X1=+4+4/4=8/2=4
X1=4
   X2=4-12=-8
4² +5²=6²
16   +25=36